2015
DOI: 10.1002/cphc.201500568
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐Dependent Electrochemical Properties of CuS Hierarchical Superstructures

Abstract: Hierarchical superstructures formed by self-assembled nanoparticles exhibit interesting electrochemical properties that can potentially be exploited in Li-ion batteries (LIBs) as possible electrode materials. In this work, we tested two different morphologies of CuS superstructures for electrodes, namely, tubular dandelion-like and ball-like assemblies, both of which are composed of similar small covellite nanoparticles. These two CuS morphologies are characterized by their markedly different electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…Similarly, CuS dandelion-like clusters were synthesized by a simple colloidal approach. 127 The authors were able to obtain such a structure by varying the solvent. When employed as an electrode in LIBs, electrochemical data indicated improved performance delivering 420 mAh g −1 at 1.12 A g −1 , and at 0.56 A g −1 , the capacity was as high as 500 mAh g −1 with good capacity retention.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, CuS dandelion-like clusters were synthesized by a simple colloidal approach. 127 The authors were able to obtain such a structure by varying the solvent. When employed as an electrode in LIBs, electrochemical data indicated improved performance delivering 420 mAh g −1 at 1.12 A g −1 , and at 0.56 A g −1 , the capacity was as high as 500 mAh g −1 with good capacity retention.…”
Section: Methodsmentioning
confidence: 99%
“…The cathodic peaks around 2.1 and 1.6 V (vs Li + /Li) are due to the two‐step reaction as shown below: CuS + Li → 1/2 Cu 2 S + 1/2 Li 2 S and 1/2 Cu 2 S + Li ↔ Cu + 1/2 Li 2 S . In the first charge process, a broad weak peak around 0.8 V corresponds to the decomposition of SEI layer, while two prominent peaks at 1.9 and 2.3 V are related to Li‐ion extraction . Therefore, it can be speculated from above analyses that the lithium‐storage performances of CuS( x wt%)@Cu‐BTC are affected by various factors such as porosity, conductivity, as well as the content and size of CuS.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effective design of such materials is still a big challenge . Recently, MOFs have been considered as ideal precursors/sacrificial templates for preparing various ordered nanostructures such as porous carbon, M/C, MO x , MO x /MO x , carbon/MO x , MS x , and MO x /MS x . Among them, MOF‐derived MS x products usually possess high surface areas for energy conversion reaction, which has opened up a new research direction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the above XRD and XPS results, it can be concluded that CuS without any impurities is affirmed. It was reported that a reversible Li + -intercalation/deintercalation process takes place at higher voltages (above approximately 1 V versus Li/Li + ) [29] through a number of intermediate phases with varying Li content. To continue the cycling series, CV and charge/discharge curves were tested in the potential range between 1 V to 3 V in this work.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%